2019
DOI: 10.1080/14658011.2019.1666465
|View full text |Cite
|
Sign up to set email alerts
|

Property improvements of EVOH by enhancing the hydrogen bonding

Abstract: Ethylene-vinyl alcohol (EVOH) with excellent barrier properties is insufficient in mechanical properties, which limits its application. For the purpose of enhancing mechanical properties of EVOH, blend of anhydrous magnesium chloride (MgCl 2 ) with EVOH was prepared by melt blending. Enhanced hydrogen bonding can be achieved through interaction between the Cl of MgCl 2 and -OH in EVOH, and the stronger hydrogen bonding between MgCl 2 and EVOH was confirmed by using Fourier transform infrared spectrometer and X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…However, for T>Tm,italicPEO$$ T>{T}_{m, PEO} $$, the higher E$$ {E}^{\prime } $$ values could only be related to the hydrogen bonding in the blends. Studies on the hydrogen bonding at high temperatures suggest that this interaction exists even at 200°normalC$$ {}^{{}^{\circ}}\mathrm{C} $$ in the form of dynamic hydrogen bonding between OH groups and electronegative atoms and functional groups 43,44 . Therefore, it can be safely assumed that the hydrogen bonding is responsible for the high‐structural stability of the blends.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for T>Tm,italicPEO$$ T>{T}_{m, PEO} $$, the higher E$$ {E}^{\prime } $$ values could only be related to the hydrogen bonding in the blends. Studies on the hydrogen bonding at high temperatures suggest that this interaction exists even at 200°normalC$$ {}^{{}^{\circ}}\mathrm{C} $$ in the form of dynamic hydrogen bonding between OH groups and electronegative atoms and functional groups 43,44 . Therefore, it can be safely assumed that the hydrogen bonding is responsible for the high‐structural stability of the blends.…”
Section: Resultsmentioning
confidence: 99%
“…42 However, suppressing the crystallization process comes with a cost and that is usually OH groups and electronegative atoms and functional groups. 43,44 Therefore, it can be safely assumed that the hydrogen bonding is responsible for the high-structural stability of the blends.…”
Section: Dynamic Behavior Analysismentioning
confidence: 99%
“…The smallest crystallite size recorded at 30-Mg(ClO4)2 proves the reduction of crystalline nature after the participation of salt in the polymer matrix. At this concentration, the crystalline peak becomes broader and lower in intensity, thus exhibiting the lowest degree of crystallinity, about 27.39%, resulting in the system's highest amorphous nature, promoting the transportation of ions in the polymer matrix [20,38]. Beyond this concentration, the degree of crystallinity is observed to become increase.…”
Section: Structural Studies Of Agarose-mg(clo4)2 Polymer Electrolytementioning
confidence: 96%
“…Several advanced studies on the effect of salts on polar polymers have been reported recently. Such polymers include ethylene-vinyl alcohol [13], bisphenol-A polycarbonate [14], poly(lactic acid) [15], polyamide 6 [16,17], poly(methyl methacrylate) [18][19][20][21], and a copolymer of vinyl butyral and vinyl alcohol [21]. Studies have revealed that the mechanical properties of these polymers are improved by the addition of a salt.…”
Section: Introductionmentioning
confidence: 99%
“…Although lithium salts have been investigated greatly as mentioned, we focused on magnesium salts for the following reasons: (1) Magnesium salts have the smallest cations and the largest lattice energies; they form the strongest and most stable ionic bonds. This contributes to the formation of strong ion-dipole interactions with PVA chains [13]. In general, the main factor that influences the lattice energy of ionic crystals is ionic charge.…”
Section: Introductionmentioning
confidence: 99%